2021
DOI: 10.1111/cfs.12831
|View full text |Cite
|
Sign up to set email alerts
|

Children expressing their views in child protection casework: Current research and their rights going forward

Abstract: Article 12 of the UN Convention on the Rights of the Child (CRC) provides children with the right to express their views in matters that affect them, particularly those of an administrative and judicial nature. This paper examines the academic discourse in child protection research concerning how Article 12 of the CRC is implemented and how it is manifested in child protection service (CPS) casework practices. The systematic review was performed following the principles of the Preferred Reporting Items for Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
1
21
1
Order By: Relevance
“…Similarly, Jones et al ( 2020 ) suggested that the pandemic would enable the reshaping of CPS to include children as part of the solution. Although listening to children's experiences enables stakeholders to better understand and respond to their needs and support their well‐being, international CPS practices lack children's voices or take a tokenistic approach to listen to children's views (Kosher & Ben‐Arieh, 2020 ; Toros, 2021 ; Falch‐Eriksen et al, 2021 ; van Bijleveld et al, 2020 ). In general, children's participation is believed to benefit both children and society (Björnsdóttir & Einarsdóttir, 2017 ), including in times of crisis.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…Similarly, Jones et al ( 2020 ) suggested that the pandemic would enable the reshaping of CPS to include children as part of the solution. Although listening to children's experiences enables stakeholders to better understand and respond to their needs and support their well‐being, international CPS practices lack children's voices or take a tokenistic approach to listen to children's views (Kosher & Ben‐Arieh, 2020 ; Toros, 2021 ; Falch‐Eriksen et al, 2021 ; van Bijleveld et al, 2020 ). In general, children's participation is believed to benefit both children and society (Björnsdóttir & Einarsdóttir, 2017 ), including in times of crisis.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…In this meta-synthesis, we summarize children’s perspectives on their participation in foster care processes and in particular their (non-) participation in the removal from home, foster family processes, and placement breakdown. The findings of this meta-synthesis will be useful to policy makers, who are increasingly requested to incorporate children’s voices into decision-making [ 16 , 24 , 25 ], and practitioners, who need to consider the nuances of when and how to include children’s voices in practice and decision-making [ 26 ]. The inclusion of children’s voices has a number of benefits to children, practitioners, and policy makers, such as affording children their inherent rights to participate, empowering children and reducing their confusion regarding services, and improving service delivery through more tailored, responsive services [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this meta-synthesis will be useful to policy makers, who are increasingly requested to incorporate children’s voices into decision-making [ 16 , 24 , 25 ], and practitioners, who need to consider the nuances of when and how to include children’s voices in practice and decision-making [ 26 ]. The inclusion of children’s voices has a number of benefits to children, practitioners, and policy makers, such as affording children their inherent rights to participate, empowering children and reducing their confusion regarding services, and improving service delivery through more tailored, responsive services [ 24 , 26 , 27 ]. As the authors of one review note, children’s “participation has both intrinsic (dignity and self-worth in terms of expressing views to influence decisions about their lives) and instrumental (policy and better outcomes for children in terms of supportive relationships with their workers and positive experiences at school and in CPS [children protection services]) value” [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations